Improving Quality of Small and Medium Entreprises Products (SMEs) through Training Product Legality on Science and Technology Program for Entrepreneurship at Muhammadiyah University of Sidoarjo - Wiwik Sulistiyowati; Ida Agustina Saidi; Nihlatul Qudus SN (Proceedings of The ICECRS, 2017)
The legality of a product is the most important thing to measure the quality indicator of a product. Through Science and Technology for Entrepreneurship Program, SMEs disabled participants are given socialization about the importance of product legality e.g. Household Food Industry (PIRT), brand, logo and halal. The purpose of this activity is to improve the quality of SME products through product legality training. The method used is quantitatif method with experiment approach. For training method used PALS (Participatory Action Learning Center) methods. The PALS method approach emphasizes on the transformation of existing activities cultivated in the changes towards the improvement of the conditions of SMEs. Stages of the PALS method approach are the awareness stage, the process of capturing product quality and accompaniment. The result is that there is an increasing number of business actors who take care of PIRT, logos and brands. It can be seen from the significance value of paired t-test results, this is at pretest condition (before taking product legality training) and posttest when tenant has attended product legality training. With a significance value of 0.000 smaller than the critical value of 0.005, then Ho (initial hypothesis) is processed, so that there are significant differences of tenant who have followed the product legality training to improve the ability of tenant in preparing documents of PIRT, brand and logo for his business